2003
DOI: 10.1038/sj.bjp.0705326
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid and arachidonic acid release in rat brain astrocytes is mediated by two separate isoforms of phospholipase A2 and is differently regulated by cyclic AMP and Ca2+

Abstract: 1 Docosahexaenoic acid (DHA) and arachidonic acid (AA), polyunsaturated fatty acids (PUFAs), are important for central nervous system function during development and in various pathological states. Astrocytes are involved in the biosynthesis of PUFAs in neuronal tissue. Here, we investigated the mechanism of DHA and AA release in cultured rat brain astrocytes. 2 Primary astrocytes were cultured under standard conditions and prelabeled with [ 14 C]DHA or with [ 3 H]AA. Adenosine 5 0 -triphosphate (ATP) (20 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
226
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(239 citation statements)
references
References 66 publications
10
226
1
2
Order By: Relevance
“…with age, whereas synthesis-secretion rates (product of conversion coefficient and unesterified plasma Introduction Docosahexaenoic acid (22:6n-3, DHA), a long-chain n-3 polyunsaturated fatty acid (PUFA), is enriched in brain and retina phospholipids, where it modulates membrane fluidity, regulates functions of membraneassociated proteins (Stubbs and Smith 1984;Salem et al 2001;Kim 2007), and participates in calciumindependent phospholipase A 2 mediated neurotransmission (Strokin et al 2003). DHA may be obtained directly from dietary sources, such as fish or fish products, or it can be synthesized from its nutritionally essential plant-derived precursor, α-linolenic acid (18:3n-3, α-LNA), through a series of elongation and desaturation steps (Sprecher 2000).…”
mentioning
confidence: 99%
“…with age, whereas synthesis-secretion rates (product of conversion coefficient and unesterified plasma Introduction Docosahexaenoic acid (22:6n-3, DHA), a long-chain n-3 polyunsaturated fatty acid (PUFA), is enriched in brain and retina phospholipids, where it modulates membrane fluidity, regulates functions of membraneassociated proteins (Stubbs and Smith 1984;Salem et al 2001;Kim 2007), and participates in calciumindependent phospholipase A 2 mediated neurotransmission (Strokin et al 2003). DHA may be obtained directly from dietary sources, such as fish or fish products, or it can be synthesized from its nutritionally essential plant-derived precursor, α-linolenic acid (18:3n-3, α-LNA), through a series of elongation and desaturation steps (Sprecher 2000).…”
mentioning
confidence: 99%
“…Three major PLA 2 enzymes occur in brainFa Ca 2 þ -dependent cytosolic cPLA 2 selective for AA, a Ca 2 þ -dependent secretory sPLA 2 , and a Ca 2 þ -independent iPLA 2 selective for docosahexaenoic acid (22:6 n-3), another polyunsaturated fatty acid found usually at the sn-2 position of phospholipids (Clark et al, 1995;Dennis, 1994;Murakami et al, 1999;Strokin et al, 2003). Although we do not know which PLA 2 enzymes mediate the k* responses to arecoline and DOI, LiCl feeding to rats is reported to downregulate brain mRNA and activity levels of cPLA 2 but not of sPLA 2 or iPLA 2 (Bosetti et al, 2001;Rintala et al, 1999;Weerasinghe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1). It has been reported that bradykinin stimulated the release of AA (37,38). Both mechanisms for the generation of AA and activation of cPLA 2 activity and AHNAK protein would convey activation of the PLC␥ isozyme.…”
Section: Discussionmentioning
confidence: 99%